Pengaruh Social Media Marketing, Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Sate Taichan Goreng - Safira Sania; Mariah (Research and Community Service UNIVERSITAS KALBIS, 2022)
This study aims to determine how much influence the social media marketing, service quality, and location on purchasing decisions on Sate Taichan Goreng. This study uses a nonprobability sampling technique. The results of 132 respondents who processed using the SPSS Statistics 13 program showed that social media marketing variables influence purchasing decisions with a calculated T value> T table = 4.242> 1.978. Service quality variable influences the purchase decision with the calculated T value> T table = 2.710> 1.978. Location variable influences the purchase decision with a calculated T value> T table = 4.316> 1.978. Variables of social media marketing, service quality, and location simultaneously influence purchasing decisions with a calculated F value> F table = 4.695> 2.675. This explains that Ho is rejected and Ha is accepted, which means that social media marketing, service quality, and location variables affect purchasing decisions partially or simultaneously.